Unveiling the charge density wave mechanism in vanadium-based Bi-layered kagome metals - Yi-Chen Yang; Soohyun Cho; Tong-Rui Li; Xiang-Qi Liu; Zheng-Tai Liu; Zhi-Cheng Jiang; Jian-Yang Ding; Wei Xia; Zi-Cheng Tao; Jia-Yu Liu; Wen-Chuan Jing; Yu Huang; et al. (NPG Asia Materials)
Abstract The charge density wave (CDW), as a hallmark of vanadium-based kagome superconductor AV3Sb5 (A = K, Rb, Cs), has attracted intensive attention. However, the fundamental controversy regarding the underlying mechanism of CDW therein persists. Recently, the vanadium-based bi-layered kagome metal ScV6Sn6, reported to exhibit a long-range charge order below 94 K, has emerged as a promising candidate to further clarify this core issue. Here, employing micro-focusing angle-resolved photoemission spectroscopy (μ-ARPES) and first-principles calculations, we systematically studied the unique CDW order in vanadium-based bi-layered kagome metals by comparing ScV6Sn6 with its isostructural counterpart YV6Sn6, which lacks a CDW ground state. Combining ARPES data and the corresponding joint density of states (DOS), we suggest that the VHS nesting mechanism might be invalid in these materials. Besides, in ScV6Sn6, we identified multiple hybridization energy gaps resulting from CDW-induced band folding, along with an anomalous band dispersion, implying a potential electron-phonon coupling-driven mechanism underlying the formation of the CDW order. Our finding not only comprehensively maps the electronic structure of V-based bi-layer kagome metals but also provides constructive experimental evidence for the unique origin of CDW in this system.